Evaluating the reality of the trend towards recreation and leisure of university residence students. - mehaouchi, Rima; bourass, mohamed; djridel , ahmed houssin (sports creativity, 2023)
The Object of the study aims to identify The reality of the trend towards recreation and leisure for university residency students, for this purpose, we used the method Descriptive survey. On a sample composed of 300 resident students Chosen as Randomly selected, and for data collection, we used a tool Questionnaire, After collecting the results and having treated them statistically, we The trend towards recreation is influenced by the leisure time culture of university residency students. Recreation has a positive effect on planning recreational programs during leisure time. Recreation also contributes to investing leisure time for university residency students. On this basis, the study recommended Attention to recreation and leisure within university residencies.